Portugal : Selected Issues. (IMF Staff Country Reports; Country Report, 2019)
This Selected Issues paper focuses on cross-country differences in savings rates in advanced European countries. It explores a range of demographic, fiscal and financial factors that could explain why household savings are low in Portugal compared to its peers. Portugal's household saving rate is lower than those of the average European country. This difference can be explained by Portugal's lower disposable income, lower financial net wealth, higher old-age dependency ratio, higher government spending on pensions and on social protection benefits, and higher homeownership ratio, as suggested by a comparison against another 14 European countries conducted with the aid of panel regressions. Other factors that could underlie Portugal's low household saving are the country's lower education levels, fertility rate, and private pension coverage. Many of these factors are not amenable to simple or direct policy interventions, although some policy initiatives aimed at higher level objectives, such as promoting economic growth, could have positive side effects on household saving. More specific policy options to boost household saving include measures to promote private occupational and personal plans, including some changes in taxation, and developing incentives to work past age 65.